PENERAPAN PERHITUNGAN BESARAN GANTI RUGI DALAM PEMBEBASAN TANAH BERDASARKAN KONSEPSI HUKUM TANAH NASIONAL - Husnaini Husnaini; Yonani Yonani (Fakultas Hukum Universitas IBA Palembang, 2021)
Marriage is the beginning of living together in a bond that is regulated in laws and regulations with the intention of forming a happy family, as mandated by Article 1 of Law Number 1 of 1974 concerning Marriage, which reads: